(untitled) (Asian Journal of Social Science Studies, 2019)
Migration is a movement of people from one region to another, at an international level the migration takes place from one country to another. Japan has a history as a country that is closed, does not want to open up with other countries. But as a result of the economic downturn, the Japanese government wants to withdraw Nikkeijin (a foreign citizen who is still of Japanese descent) to return to Japan and work in Japan. Brazilian Nikkeijin has a history with Japan where the early history of the Japanese population immigrated more to Japan, led by Kasato Maru. Hamamatsu City, Japan, is Japan’s most industrialized city entered by the Brazilian Nikkeijin. There is a network influenced by an increase in migrants in Hamamatsu, Japan. This study analyzes the network in increasing Brazilian migrants in Hamamatsu, Japan in 2000-2006 using network theory proposed by Doughlas S. Massey.